The Life of a Tidal Blade under Fatigue Testing (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Fatigue in composite tidal turbine blades is a significant challenge that can significantly affect the long-term efficiency and structural integrity of tidal energy turbines. Numerical simulations of fatigue behaviour are computationally intensive and are often limited by assumptions and uncertainties that undermine the reliability of blade designs. Offshore mechanical testing, which replicates oceanic loading conditions under controlled environments, provides a promising solution for accurately measuring fatigue under realistic conditions. However, challenges persist, particularly in synchronizing cyclic loads with the blade's natural frequency and managing thermal issues associated with testing composite materials at high frequencies. Traditional hydraulic systems, which are typically used for applying loads, are energy-inefficient and costly. To address this, the FastBlade fatigue testing facility employs a regenerative digital displacement hydraulic pump system, offering up to 75% energy savings while ensuring precise control over the testing process.This study explores the fatigue testing of a composite tidal turbine blade using single and multiple actuators operating at frequencies up to 3 Hz, arriving until the failure of the bade. The testing was coupled with Reynolds-Averaged Navier-Stokes (RANS) simulations based on collected water velocity data to define target loads. Measurements taken during testing provided valuable insights into blade behaviour and testing protocols.  Variations in tip displacements and strain responses highlighted the need for improved testing procedures, especially before failure. The analysis of this data will be instrumental in refining FastBlade's testing protocols, particularly regarding control strategies, load introduction methods, instrumentation layout, and calibration, ultimately enhancing the reliability and performance of tidal turbine blade testing.The findings of this research contribute significantly to advancing the understanding of fatigue testing in tidal turbine blades. The study lays the groundwork for future improvements in blade design and performance validation by integrating real-world testing with computational fluid dynamics and simulations. These advancements will help develop more efficient, durable tidal energy turbines, facilitating the growth of the tidal energy industry. The tidal energy sector can expect to achieve more reliable and cost-effective solutions for harnessing ocean energy with the continued refinement of testing protocols, including energy-efficient loading methods and more accurate fatigue modelling.